The Influence Of Service Quality On Patient Satisfaction At Sukahaji Majalengka Health Center - Maryani Thiolisda Simanjuntak; Farida Yuliaty; Rulia , Rulia (Jurnal Scientia, 2024)
Puskesmas, as a health service institution, aims to pay attention to the promotion and prevention of disease, as well as individual health services at the initial level, is a center for community health development which has the responsibility to care for public health in the area under its responsibility, and is important for ensuring patient satisfaction. can influence subsequent behavior in using these health services, while the quality of health services needs to be improved to meet standards by utilizing resources efficiently, effectively within the limits of the Government and community's capabilities, so as to create service user satisfaction which forms a harmonious relationship between service providers and customers. The lack of health facilities, including adequate medical equipment, as well as delays in services due to a shortage of medical personnel, have resulted in decreased patient satisfaction at the Sukahaji Community Health Center, Majalengka Regency. The aim of this research is to examine and analyze service quality and patient satisfaction as well as the influence of the relationship between these variables at the Sukahaji Community Health Center. The research method used is a quantitative method with multiple linear analysis. Service quality variables, including Tangible, Empathy, Reliability, Responsiveness, and Assurance, received high ratings, as did patient satisfaction. Tangible, Reliability, and Assurance have a positive and significant influence on patient satisfaction, while Empathy and Responsiveness have a positive but not significant influence. Overall, the high quality of service collectively contributes to patient satisfaction at the Sukahaji Community Health Center, Majalengka.